Factors influencing the popularity of hiligaynon magazine. - Torema, Bemjo Torres (2011.)
This study is entitled Factors Affecting the Popularity of Hiligaynon Magazine. Its objectives were to determine the factors within the editorial board and among readers and non-readers of the said magazine that can influence its popularity in Iloilo City, using the Limited Effects Theory and the Uses and Gratifications Theory. A total of 83 respondents were surveyed in Iloilo City and further divided according to their experience with Hiligaynon magazine: (1) recent readers, (2) past readers, (3) non-readers and (4) non readers who are aware of Hiligaynon magazine. Content is the primary reason of recent readers for patronizing Hiligaynon magazine. Most past readers no longer read Hiligaynon magazine because they thought it had stopped publication in the 1970's. Content was also the primary reason why they used to read it in the past. Among non-readers who were aware that there is a Hiligaynon magazine in the market, the most frequent reason why they did not read it was because of lack of information and availability. The researcher also held a telephone interview with the magazine's Associate Editor Mr. Ner E. Jedeliz Jr. and as a conclusion, which determined a lack of promotion and advertising within Iloilo City.
Research Project (Undergraduate, Bachelor of Arts in Communication and Media Studies) College of Arts and Sciences, UP Visayas, Miagao, Iloilo
Keywords: Magazine, Hiligaynon